Rumours as moral action: Contesting the local state through housing in China. (June 2018) - Bruckermann, Charlotte
In China's Shanxi Province, responses to an earthquake rumour translated mundane concerns over safe, adequate, and affordable housing into mass action during a perceived emergency. Ongoing housing rumours challenged the wider political-economic sphere that promised order and harmony through regulations, yet frequently led to inequality and even chaos in practice. In order to understand the morality underlying the circulation of these rumours, the article explores the Chinese realm of minjian as a domain of mutual solidarity safeguarding kin, acquaintances, and even strangers. It compares this realm of minjian to E.P. Thompson's notion of 'the crowd', as sites of mass action due to diminishing access to a means of livelihood under conditions of marketization. The article thereby reflects on the transformation of Chinese homes from domestic spaces of safety and security to vehicles for capital accumulation subjected to risky speculation and dangerous corruption.